A Semantic Study of Iraqi Personal Names and Beyond - Elaf Fkran Ismael , Asst. Inst.; Ruqaya Issa Mahmood , Asst. Inst. (lark, 2023)
Iraqi names are simply one aspect of this investigation. The name selection is done by using a suitable evaluation of the process. In addition, it offers rationality and a purpose beyond them. The influencing factors for name selection are thoroughly described. Only names from Iraq are included in the study. During the 2022–2023 academic year, the data were gathered from English Department students at Samarra University’s College of Education. It is significant to mention that the students originate from different cultural backgrounds, including cities and towns in middle and south Iraq. The data include not only the names of the students but also details about their siblings and other family members who were born after 2000 AD. Therefore, this study looked into the meaning of Iraqi personal names and beyond.